Contemporary Biology Understood from Science, Technology and Innovation (2020)
This article is based on a documentary review of some aspects related to the configuration of the living and life in the present in relation to advances in science and technology, indispensable for the impulse of vitality and productivity. The analytical lens used was the notion of counterbehavior taken from Michel Foucault’s toolbox, which makes visible what conditions make possible to activate the behaviors of the subjects in relation to the living and life, among which emerge, research as a practice of counterbehavioral thinking, transversal axis of the text that, on the one hand, allows to glimpse and reflect on some contemporary problems of biology, and the another hand, it shows that both DIYbio and biohacking propose alternative ways of approaching science and technology in order to problematize the relationships we have consolidated with the world. These questions propose other readings and ways of relating the living and life that broaden the gaze on biology and its teaching, which is fundamental to understand the contemporary issues in which we participate.